A Health Literate Healthcare Organization Index System for China: Based on CiteSpace and Qualitative Analysis - Zhao S; Chen Y; Xia X; Zhou J; Wang X; Sun Q; Chang J; Ge J; Hu L; Lu R (Journal of Multidisciplinary Healthcare)
Shenyu Zhao,1,* Yang Chen,2,* Xiyang Xia,2 Jing Zhou,2 Xiaoyu Wang,2 Qing Sun,1 Jiaqian Chang,2 Jiaying Ge,2 Lingmin Hu,2 Renjie Lu1,3 1Changzhou Third People’s Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China; 2Department of Reproduction, Changzhou Maternity and Child Health Care Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China; 3Changzhou Institute for Advanced Study of Public Health, Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Renjie Lu, Changzhou Third People’s Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, 213000, People’s Republic of China, Email renjie_lu@126.com Lingmin Hu, Department of Reproduction, Changzhou Maternity and Child Health Care Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, 213000, People’s Republic of China, Email hulingmin1986@126.comObjective: This study aims to analyze the current status and development trends of health literate healthcare organization (HLHO) worldwide, and preliminarily construct an index system suitable for HLHO in China.Methods: This study first utilized CiteSpace for bibliometric analysis to explore global research hotspots and trends in HLHO. Based on these findings, expert opinions were gathered through focus group interviews to preliminarily develop the index system. Finally, semi-structured interviews in primary hospitals were conducted to optimize the system, assess its adaptability, and collect feedback for refinement.Results: CiteSpace bibliometric analysis identified high-frequency themes—including health literacy, education, service, communication, health information, digital healthcare, special populations, community, and management—as the primary indices of HLHO. Based on expert input from focus group discussions, an index system comprising 14 primary and 120 secondary indices was developed, covering key domains such as organizational management, health education, provider–patient communication, self-management, digital services, and support for vulnerable groups. Further expert interviews indicated that the system also had good local adaptability and strong potential for broader implementation in primary hospitals.Conclusion: The index system developed in this study provides both a theoretical framework and a practical tool to support the standardized construction of health-literate healthcare organizations in China. It not only integrates cutting-edge international experience but also aligns with the practical needs of the Chinese healthcare context, demonstrating strong adaptability and relevance. The system is expected to facilitate hospital self-assessment, quality improvement, patient support, and health education efforts, thereby laying a solid foundation for enhancing healthcare service quality and improving patients’ health literacy. Moving forward, our research team will continue to optimize the index system for practical use, and initiate multicenter pilot studies and quantitative scale development to strengthen its operability and value for broader implementation.Keywords: health literate healthcare organization, CiteSpace, focus group interviews, index system